Cara Cepat Membaca Al Quran melalui Metode Yanbu' - Djunaidi Djunaidi; Ainul Hanif (Transformasi : Jurnal Studi Agama Islam, 2022)
Recently, there are many ways on how to read the Quran. The aim is to make it easier for students to quickly read the Quran. The purpose of this study is to determine the application of the Yanbu method in the Quran reading learning process, to understand the advantages and disadvantages of the Yanbu method, and to formulate teacher tips to improve students' abilities in the reading learning process. Quran. This research adopts qualitative method and qualitative descriptive research method. The results show: The application of the Yanbu method in the learning process of reading the Quran, 1) Beginning with prayers in the guide, recitation of short verses, classic reading, Sorogan activities, homework, daily assessment. 2) Advantages of Yanbu Afa, Arabic rolls are more complete than other methods, making it easier for students to learn the Arabic alphabet, tones are used when reading classics/songs, complete and structured learning materials are available every day according to the age of the student learn to write pegon, learn to evaluate activities. 3) The learning process at this school is not formally written, and there is no written lesson schedule. 4) Teachers can help students improve their ability to read the Qur'an by practicing it over and over again.